Основы логики: учебник / В. А. Бочаров, В. И. Маркин - Бочаров Вячеслав Александрович (ИНФРА-М, 1998)
Экземпляры: ЧЗ (20160120) / Инвентарный номер: 33571 / Цена: 24.19 / Авт.знак: Б 86 / ГРНТИ: 02 / ББК: 87.4